Exploring the potential macroeconomic impacts of branch banking practices - Davíð Steinar Guðjónsson 1983- (2014)
The role that the internal structure of a Bank's ledger, in particular the interaction between ledger operations between its branches and internal rules governing lending plays in determining local lending limits has been generally ignored in economic analysis. Typically modern banks use a branch banking structure where several branches, in different catchment areas, operate under a single general ledger. We suspect that internal branch banking practices and modern regulatory frameworks are a possible cause of a disparity seen in empirical data from Iceland for 1997 - 2004, which show lending and liability deposits growing slower outside of the capital area than inside it. In this thesis we explore this possibility through a series of simulations, focusing on the impact of a hypothetical branch lending restriction, where a branch is restricted to not lend more than its deposits. The result of this thesis indicates that internal restrictions surrounding branch banking can contribute to disparities in monetary expansion between catchment areas. The simulations are performed using a double entry bookkeeping level banking simulator Threadneedle, within a simplified economic model in order to isolate the behaviour of the banking system. This may provide an explanation for higher real estate prices being observed in the financial capital in countries where branch banking is dominant and branch banking head offices are concentrated. The general conclusion of this work is that branch banking has been underexplored and needs to be revisited in the light of its interaction with modern regulatory frameworks. Það hlutverk sem innra skipulag höfuðbókar banka, einkum samspil bókfærsla milli útibúa og innri reglur útlána, spilar í að ákvarða svæðisbundin útlán hefur almennt verið hundsuð af hagfræðinni. Venjulega nota nútímabankar útibúabankaskipulag þar sem nokkur útibú, á mismunandi svæðum, starfa undir einni höfuðbók. Okkur grunar að innri starfshættir útibúa og nútíma regluverk séu möguleg orsök mismunar sem sést í ...